О некоторых аспектах взаимоотношений Карагандинского обкома компартии и высших учебных заведений региона в 1940-х и начале 1950-х годов (история в архивных документах) - Капышев, А.К. (Изд-во КарГУ, 2012)
1940-шы мен 1950-жылдар басындағы аймақтық биліктің (Қарағанды облыстық комитет компартиясы негізінде) Қарағандының жоғары оқу орындарымен байланыстарының нəтижелері мұрағат құжаттары негізінде талданады. Белгілі кезеңде жоғары оқу орындарында аймақтық саясат билігі қадағалауында болған, қудаланған, репрессивті немесе «əлеуметтік сəйкес емес» оқытушылар қызмет еткен. Мақаланың орталық идеясы қудаланған ғалымдар соңынан облыстық комитет компартиясы тарапынан əрдайым қадағалау жүргізілгені жөнінде болып отыр. Біздің көзқарасымыз бойынша, бұл жағдай Қарағанды жəне оның аймақтық билігіндегі ерекшеліктердің бірі болған. On the basis of archives’ documents the relationships of regional authorities (in the name of Karaganda regional committee of the Communist party) with Karaganda higher educational institutions during 1940-s to the beginning of 1950-s have been analyzed. In the given period in a number of higher institutions (Karaganda pedagogical institute, Karaganda medical institute) worked the exiled, the repressed and by the origin «socially neglected» teachers who were under supervision of regional and political authorities. The central idea of the article is to show that the exiled scientists were under permanent control by regional committee of the Communist party. However, the «organizational summaries» were not done as well. In our opinion we consider it the most characteristic feature of Karaganda and regional Karaganda authorities.
About some aspects of mutual relations between Karaganda region committee of communist party and regional higher education institutes in 1940s and early 1950s (history in archive documents)